2015
DOI: 10.1186/s12906-015-0695-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and modes of complementary and alternative medicine use among peasant farmers with musculoskeletal pain in a rural community in South-Western Nigeria

Abstract: BackgroundAnecdotally, use of Complementary and Alternative Medicine (CAM) for Musculoskeletal Pain (MSP) is common in Nigeria; however, there seems to be a dearth of empirical data on its prevalence and mode of use. This study investigated the prevalence and modes of use of CAM for MSP among farmers in a rural community in South-western Nigeria.MethodsThis cross-sectional survey employed multistage sampling technique guidelines for conducting community survey by the World Health Organization among rural commu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 44 publications
3
23
0
Order By: Relevance
“…However, this contrast with the study of Singh, Raidoo & Harries 7 among the Indians in South-Africa, whose study showed a very low prevalence CAM use rate (38.5%). Nonetheless, findings from this study is similar to that of Onyiapat et al, 17 and Mbada et al, 19 studies where they found a very high prevalence of CAM use; 84.7% and 96.8% respectively. Findings from this study revealed the use of CAM to be most common among people aged 30-34.…”
Section: Discussion Of Findingssupporting
confidence: 91%
See 1 more Smart Citation
“…However, this contrast with the study of Singh, Raidoo & Harries 7 among the Indians in South-Africa, whose study showed a very low prevalence CAM use rate (38.5%). Nonetheless, findings from this study is similar to that of Onyiapat et al, 17 and Mbada et al, 19 studies where they found a very high prevalence of CAM use; 84.7% and 96.8% respectively. Findings from this study revealed the use of CAM to be most common among people aged 30-34.…”
Section: Discussion Of Findingssupporting
confidence: 91%
“…7,17,18 Similarly, the few studies that have been conducted in Nigeria were done in the South-west and South-East in Nigeria. 19 This phenomenon of CAM use among pregnant women is yet to be explored in detail among the people of the South-South. Therefore, it is expedient to examine this issue among pregnant women in Bayelsa and Rivers State which are in the South-South part of Nigeria.…”
Section: Introductionmentioning
confidence: 99%
“…7,8,11,12 Varying prevalence of CAM use in rheumatic patients is reported from different countries-United States two third of respondents, Australia 40%, Turkey 46% and India 58%. [13][14][15] In a study to define the relationship between medical skepticism and CAM use in two groups of individuals with musculoskeletal disorders; those being served by family practitioners and those served by specialists, 88% of the samples used some form of CAM for their pain related to musculoskeletal disorders.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that the use of CAM is prevalent among patients with rheumatic diseases, with the frequency of CAM use being reported as between 22% to 96.8 % depending on the country. [6][7][8] Limited information about utilisation pattern of CAM in musculoskeletal disorders is available in India. Hence this study was planned with the aim of assessing the prevalence and pattern of the utilization of CAM in Out Patient Department of Orthopaedics at a tertiary care teaching hospital in Western part of India in Gujarat state.…”
Section: Introductionmentioning
confidence: 99%
“…The high prevalence of usage of this class of CAM is not surprising as earlier studies showed a high prevalence as well. In a study among peasant farmers in south western Nigeria, 80.1% (173) was found to have used massage as a therapy (Mbada et al, 2015). The reason for the relatively low odds of use manipulative and body-based therapy by pharmacists requires further research.…”
Section: Manipulative and Body-based Therapymentioning
confidence: 99%